Contagious You: Unlock Your Power to Influence, Lead, and Create the Impact You Want - Anese Cavanaugh (McGraw Hill-Ascent Audio, 2019)
Drawn from Cavanaugh's proprietary approach to leadership, Intentional Energetic Presence® (IEP Method®), Contagious You shows readers how to "own" their leadership and effectively guide, inspire, and serve those around them. Insightful stories and real-life examples address the areas of team, dealing with failure, leading and changing culture, designing relationships, navigating conflict, transforming burnout, cultivating mindset, and more.